Interinstitutional agreement for the academic year 2012/2013 Lifelong Learning Programme, higher education (Erasmus) between Università degli Studi di Genova and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Lifelong Learning Programme / Erasmus. - Subject area: Design (graphic design, industrial design, fashion, textile); Architecture.